Comparative Analysis of the Corrosion and Mechanical Behavior of an Al-SiC Composite and AA 2024 Alloy Fabricated by Powder Metallurgy for Aeronautical Applications - Willian Aperador; Jonnathan Aperador; Giovany Orozco-Hernández (Metals)
This study presents a comparative analysis of the corrosion and mechanical properties of an Al-SiC composite and an AA 2024 aluminum alloy, focusing on their suitability for aeronautical applications. The Al-SiC composite was fabricated using advanced powder metallurgy techniques, incorporating a 20% volume of silicon carbide (SiC) particles, averaging 1.6 µm in size, to enhance its structural and electrochemical performance. Electrochemical evaluations in an aerated 3.5% NaCl solution revealed a significant improvement in the corrosion resistance of the Al-SiC composite. This enhancement is attributed to the cathodic nature of the SiC particles, which promote the formation of a protective aluminum oxide layer, reducing pitting corrosion and preserving the material’s structural integrity. In terms of the mechanical properties, the Al-SiC composite demonstrated a higher yield strength and ultimate tensile strength compared to the AA 2024 alloy. While it exhibited a slightly lower elongation at failure, the composite maintained a favorable balance between strength and ductility. Additionally, the composite showed a higher Young’s modulus indicating improved resistance to deformation under load. These findings underscore the potential of the Al-SiC composite for demanding aerospace applications, offering valuable insights into the development of materials capable of withstanding extreme operational environments.